2016
DOI: 10.3109/09273948.2015.1133840
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Uveitis in the Central Tokyo Area (2010–2012)

Abstract: When compared with years 2004-2009, the present series showed an increasing trend of intraocular malignant lymphoma, bacterial endophthalmitis, and chronic iridocyclitis, and a notable increase in chronic iridocyclitis in young girls, with decreasing trends of scleritis and Vogt-Koyanagi-Harada disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
1
10
2
Order By: Relevance
“…Consequently, the number of definite diagnoses has been gradually increasing [ 2 ]. However, a definite diagnosis can still not be reached in approximately 30–40% of patients newly diagnosed with uveitis [ 2 , 4 , 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the number of definite diagnoses has been gradually increasing [ 2 ]. However, a definite diagnosis can still not be reached in approximately 30–40% of patients newly diagnosed with uveitis [ 2 , 4 , 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 shows the frequencies of TOP4 as percentages and order in the reports from other facilities 5,7,9,1014. Several reports from Japan, as well as from other parts of Asia, and from Europe and North America are shown.…”
Section: Resultsmentioning
confidence: 99%
“…For example, compared with patients before 2010, recent patients in Singapore showed a higher percentage of infectious uveitis [26]. Studies in Japan have revealed that 35-63% of uveitis cases were noninfectious, and 31-50% were idiopathic [7,[27][28][29][30][31][32]. These studies have also demonstrated that the patterns and specific entities of uveitis, including endophthalmitis, sarcoidosis, Bechet's disease, VKH disease, and anterior uveitis, have changed with time.…”
Section: Epidemiology and Distribution Of Etiologiesmentioning
confidence: 99%
“…A study from Tokyo University Hospital indicated a decrease in patients with VKH disease from 6.3% in 2004-2006 to 4% in 2010-2012. The authors attributed this finding to the increase in optical coherence tomography in communitybased clinics, making diagnosis easier and allowing more patients to be treated rather than referred to university hospital-based clinics [31]. Gender predilection of VKH disease seems to vary globally.…”
Section: Epidemiologymentioning
confidence: 99%